Economic Conditions and Child Abuse - Jason M. Lindo; Jessamyn Schaller; Benjamin Hansen (Institute for the Study of Labor (IZA), 2013)
Although a huge literature spanning several disciplines documents an association between poverty and child abuse, researchers have not found persuasive evidence that economic downturns increase abuse, despite their impacts on family income. In this paper, we address this seeming contradiction. Using county-level child abuse data spanning 1996 to 2009 from the California Department of Justice, we estimate the extent to which a county's reported abuse rate diverges from its trend when its economic conditions diverge from trend, controlling for statewide annual shocks. The results of this analysis indicate that overall measures of economic conditions are not strongly related to rates of abuse. However, focusing on overall measures of economic conditions masks strong opposing effects of economic conditions facing males and females: male layoffs increase rates of abuse whereas female layoffs reduce rates of abuse. These results are consistent with a theoretical framework that builds on family-time-use models and emphasizes differential risks of abuse associated with a child's time spent with different caregivers.
Keywords: I10; J13; J16; J63; K42; 330; child abuse; recessions; job loss; time use; gender; childcare; Kinder; Gewalt; Konjunktur; Väter; Kriminalität; Kalifornien